The formation mechanism of metal-ceramic interlayer interface during laser powder bed fusion - Yao, Liming (2024)
Experiments on Laser powder bed fusion (LPBF) of powdered Ti on Al2O3 substrate were conducted and the interface formation was studied using a multi-material fluid dynamics model. Results show that the melt pool is relatively shallow, with relatively flat interlayer interface under LPBF’s conduction mode. In this condition, a thin sheath of molten Al2O3 forms and acts as a lubricating film for the molten Ti, leading to Rayleigh instability due to high flow inertia. Keyhole formation penetrates the Al2O3 substrate, resulting in a wavy interlayer interface. The recoil pressure from the keyhole and overall melt inertia are suppressed by the highly viscous molten Al2O3, thereby improving single-track melt pool stability. However, the thermal expansion coefficient difference between Ti and Al2O3 led to the formation of transverse cracks. Achieving a defect-free metal-on-ceramic single track remains a challenge, despite this study serving as a guide for melt track and interface control.